Human immunodeficiency virus-specific cytotoxic responses of seropositive individuals: distinct types of effector cells mediate killing of targets expressing gag and env proteins - Riviere, Y; Tanneau-Salvadori, F; Regnault, A; Lopez, O; Sansonetti, P; Guy, B; Kieny, M P; Fournel, J J; Montagnier, L (Journal of Virology, 1989)
Article Usage Stats Services JVI Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue Spotlights in the Current Issue JVI About JVI Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JVI RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0022-538X Online ISSN: 1098-5514 Copyright © 2014 by the American Society for Microbiology. For an alternate route to JVI .asm.org, visit: JVI